2014
DOI: 10.1007/s11012-014-9874-4
|View full text |Cite
|
Sign up to set email alerts
|

Time delay Duffing’s systems: chaos and chatter control

Abstract: The effect of a delay feedback control (DFC), realized by displacement in the Duffing oscillator, for parameters which generate strange chaotic Ueda attractor is investigated in this paper. First, the classical Duffing system without time delay is analysed to find stable and especially unstable periodic orbits which can be stabilized by means of displacement delay feedback. The periodic orbits are found with help of the continuation method using the AUTO97 software. Next, the DFC is introduced with a time dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As the control uses the current state and one delay period, when the perturbation is small it presents low-quality stabilization, for example during high periodic orbits [27].…”
Section: Tdasmentioning
confidence: 99%
“…As the control uses the current state and one delay period, when the perturbation is small it presents low-quality stabilization, for example during high periodic orbits [27].…”
Section: Tdasmentioning
confidence: 99%
“…In order to demonstrate the proposed method for solving the fractional order derivatives and/or delayed systems, three numerical examples which have been taken from recent publications (Leung, Guo, and Myers 2012;Leung, Yang, and Zhu 2014;Rusinek, Mitura, and Warminski 2014) are considered. The equations of motion are given by:…”
Section: System Equations Of Motionmentioning
confidence: 99%
“…The structural parameters is taken from an example in Eq. (7) of Rusinek, Mitura, and Warminski (2014). The first ten integer harmonic numbers are kept in the multiharmonic expansion, otherwise metioned.…”
Section: Optimization Problem Formulationmentioning
confidence: 99%
“…From the current theoretical researches and experimental verifications, we found that chattering impact leads to energy transfer and dissipation, causes the system vibration and noise, and reduces mechanical efficiency. Accordingly, many scholars have devoted to the study of chattering prediction and suppression, reducing or eliminating the harm of chattering-impact vibration to the system [25][26][27].…”
Section: Introductionmentioning
confidence: 99%